2018
DOI: 10.1016/j.msard.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Common comorbidities and survival in MS: Risk for stroke, type 1 diabetes and infections

Abstract: Given the high risk for stroke in this MS population and the observed complexity among the coincident common risk factors for circulatory diseases, the high risk for type 1 diabetes and common infections raise a need to recognize patients at risk with these conditions and with the other known risk factors such as metabolic syndrome and smoking. The survival disadvantage related to circulatory diseases observed in general population is true also in MS and should be recognized to reduce the burden of disease and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
(30 reference statements)
2
26
0
1
Order By: Relevance
“…These results confirm the survival disadvantage reported for cerebrovascular diseases among MS patients in a Danish study (85). Additionally, a recently published large study from Finland showed that the mean survival time is lower for MS patients with any circulatory disease (86). Among the NARCOMS registry participants, vascular, mental, and visual comorbidities increased the risk of mortality (87).…”
Section: Effect Of Comorbidities On Mortalitysupporting
confidence: 80%
“…These results confirm the survival disadvantage reported for cerebrovascular diseases among MS patients in a Danish study (85). Additionally, a recently published large study from Finland showed that the mean survival time is lower for MS patients with any circulatory disease (86). Among the NARCOMS registry participants, vascular, mental, and visual comorbidities increased the risk of mortality (87).…”
Section: Effect Of Comorbidities On Mortalitysupporting
confidence: 80%
“…Recent studies suggest an increased risk of cardiovascular events in patients with MS. 7 , 18 24 Although the literature is still incomplete and partially contradictory, some larger population-based studies suggest that MS patients have a higher prevalence of cardiovascular diseases (CVD) and a slightly increased CVD mortality risk. 18 , 19 , 22 , 25 In addition, a recent Swedish cohort study found that venous thromboembolic disorders in progressive MS accounted for a substantial proportion of this risk.…”
Section: Introductionmentioning
confidence: 99%
“…2 Physical and mental comorbidities represent significant concerns in MS, since they negatively impact quality of life and clinical outcomes in patients and may contribute to increased adverse risks in patients receiving disease modulatory therapies (DMTs). 3 Compared to the general population, a higher proportion of MS patients are diagnosed with physical conditions such as inflammatory bowel disease, acute infections, malignancies, diabetes, fractures, and hyperlipidemia, [3][4][5][6][7][8][9][10][11][12] as well as mental disorders such as depression, bipolar disorders, and anxiety. 3,[13][14][15][16][17] contradictory, some larger population-based studies suggest that MS patients have a higher prevalence of cardiovascular diseases (CVD) and a slightly increased CVD mortality risk.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS), a complex and chronic neurological disease, has been associated with coexisting diabetes mellitus (types 1 and 2), hypertension and other cardiometabolic disorders, as well as depression and other mental health disorders. 13 Although the causal directions are not clear, evidence is emerging on the key risk and protective factors influencing the burden of MS and its comorbidities, including community characteristics and built environments that favour or hinder physical activity in daily life. 4–6 In Canada, prevalence of MS is high; however, research into factors that may shape provincial differences in MS outcomes is limited.…”
Section: Introductionmentioning
confidence: 99%